Effect of Sulphur and Zinc Fertilization on Growth, Yield, and Yield Attributes of Greengram (Vigna radiata L.) under Eastern Uttar Pradesh Conditions - Nitin Sharma; Pankaj Singh; Alok Kumar Singh; Kumar Anshuman; K. N. Rai; Sarita Devi Gupta; Ankit Singh; Susheel Kumar Srivastava (International Journal of Scientific Research in Science and Technology, 2025)
The present study was conducted to study the effect of Sulphur and Zinc application on Growth and Yield of Green Gram (Vigna radiata L.) under eastern Uttar Pradesh condition. The treatments considered consisted of four levels sulphur (0, 15, 30, and 34 kg/ha) and four levels zinc (0, 5, 10, and 15 kg/HA) making sixteen treatment combination and was laid out in factorial randomised block design with three replications. The treatment combinations were evaluated for their effect on growth, and yield greengram of different treatment combinations. The results showed that application of 30 kg S/ha along with 5 kg Zn/ha proved to be the most remunerative and economical dose for getting the higher yield of the greengram under the eastern U.P. condition.
Keywords: Green Gram; Sulphur; Zinc; Mini-Nitrogen Plant; Pulses